Impacts of future weather data on the energy performance of buildings in the context of urban geometry - Mangan, Suzi Dilara; Koçlar Oral, Gül (Informa UK Limited, 2020)
Cities that expand and grow with new areas allowed for construction as a result of a rapidly increasing population have become the centre of global energy consumption. Most of the energy consumed is still based on fossil fuels, which is considered the most important cause of the rise in greenhouse gases and thus the deepening climate crisis. Therefore, the transformation of urban areas into energy-efficient and low-carbon cities has become a necessity to create a sustainable future. The climate data-based evaluation of the relationship between buildings, which have the largest energy-saving potential, and urban geometry, which affects the energy performance of buildings in the long term, is crucially important. This study aims to evaluate the potential impacts of climate change on the energy performance of buildings at the settlement scale. For this purpose, changes in building energy performance within different settlement pattern alternatives created for Istanbul (a temperate-humid climate), where new settlement patterns are rapidly developed, were evaluated according to present and future weather files. The evaluation results have demonstrated that sustainable energy use in urban areas is only possible through the integration of a building’s energy performance, urban geometry and climate change in the planning and design stages.
Keywords: building energy performance; future weather files; parametric design; TA1-2040; urban geometry; Engineering (General). Civil engineering (General)